Delay Equalization for Analog Filters with Particle Swarm Optimization - Çelik, Çağrı; Uygur, Atilla (My University, 2025)
Electronic filters are widely used in various fields such as signal processing, communication and control systems. These filters are circuits that block unwanted frequency components in the signals applied to their inputs while allowing the desired components to pass. When a signal is processed through a filter circuit, a natural delay occurs, and the signal is transmitted to the output with a delay. Ideally, this delay should have a constant value within the passband. Otherwise, the filtered electrical signal obtained at the output of the filter is distorted, and meaningful output cannot be achieved. In this paper, it is aimed to achieve the desired constant delay under ideal conditions. To approximate the ideal delay value as closely as possible in a filter that does not have a constant delay, first and second-order allpass filter blocks were cascade-connected. Allpass filter blocks only shift the signal in time without affecting its frequency magnitude response. Three parameters are used in the design of these allpass filter blocks. Particle Swarm Optimization (PSO) was used to determine these parameters. Based on the principle that living creatures in nature are more successful when they move in swarms compared to when they move individually, the PSO algorithm was preferred due to its rapid and successful results and ease of implementation. During the testing phase, the delay values of the 5th-order Chebyshev lowpass filter were examined before and after the delay equalization process. The fluctuation in the delay value was successfully reduced by %84.11. This result demonstrated the success of the algorithm used in determining the parameters and the delay equalization process.
Keywords: Active Analog Filters; Delay Equalization; Particle Swarm Optimization (PSO).